(untitled) (Konferensiyalar | Conferences, 2024)
Authentic materials have a number of advantages and provide unusual, appealing and new materials which motivate pupils to improve their reading skill. The main intention of this article to explore variety of authentic materials which are implemented in teaching reading. Theoritical points and ideas which stated by experts and scientific authors in this sphere are made discussions and contradictions in terms of availability of authentic materials for young learners. More than being this point, this research investigates appealing and challenging methods and tasks so as to utilize authentic materials to enhance reading for junior school pupils. After reviewing all literatures, this article gives precise data about the effectiveness of authentic materials in teaching reading for elementary level students.